Hanseniasis With Gilbert′s Syndrome : A Therapeutic Dilemma? - Ghosh Sanjay (Wolters Kluwer Medknow Publications, 2000)
Therapeutic dilemma often arises in leprosy patients developing jaundice as most of the anti-hanseniasis medicines are hepatotoxic. One 26 year old lady and another 21 year old male having paucibacillary leprosy developed signs of jaundice after onset of treatment with multidrug (MDT) and then they discontinued it. MDT was reintroduced and successfully continued for 6 months with pre-and post- therapy monitoring of liver function test, haemoglobin and other relevant parameters. Total bilirubin (TB) reached maximum upto 3.6 comprising predominantly of unconjugated (3.1); other parameters were normal . The third patient 64 year old male with multibacillary leprosy having past history of recurrent jaundice has also been treated for last 8 months till date with MDT by monitoring. Highest peak of TB was 4.2, unconjugated being 3.4. These represented cases of Gilbertâ€s syndrome which is a common, benign, familial unconjugated hyperbilirubinaemia without overt haemolysis are often precipitated by drugs. Partial deficiency of bilirubin glucuronosyltransferase is the main causative factor. Hence all patients of leprosy with jaundice does not need discontinuation of therapy. Some patients may have underlying Gilbertâ€s syndrome when MDT can safely be continued with monitoring.